Pengembangan Sumber Daya Manusia di Satuan Polisi Pamong Praja Balikpapan dalam Melaksanakan Tugas Penertiban Masyarakat - Amanda Fitriyanti; Ovigeria Subroto Sinaga (Journal of Management and Creative Business, 2024)
This study examines the development of human resources (HR) carried out by the Balikpapan Civil Service Police Unit (Satpol PP) in the context of implementing community control tasks. Through a qualitative approach by applying data collection techniques in the form of in-depth interviews and observations. The result of the research shows that Balikpapan Satpol PP has implemented various human resource development programmes, such as training and education, in order to improve the competence and professionalism of its members. In addition, this study suggests that there is a significant relationship between human resource development and the ability of Satpol PP in carrying out community policing tasks.